Recent advances in surface-modified cellulose nanofibrils - Rol, F.; Belgacem, M. N.; Gandini, A.; Bras, J.
The production of nanocellulose has garnered increased attention in the past decades and is now the second-ranked priority of the European bioeconomy. The number of papers published on nanocellulose has increased by six fold in the last five years and studies on nanofibrillated cellulose (CNF)represent nearly 65 percent of that literature. Studies in the most recent years have focused on CNF production at industrial scales, since it is hampered by high energy consumption and cost. Chemical pretreatment of cellulose fibers is essential to improving nanofibrillation and decreasing energy consumption. Moreover, functionalized CNFs and bacterial cellulose (BC)endowed with additional properties are expected to be used for high-value added applications. This nanoscale material is bio-based, biodegradable, and biocompatible with very promising barrier and mechanical properties, although its high hydrophilicity is a limiting factor for some applications. CNF and BC modification is also a key step to improve its compatibility with different macromolecular matrices in the elaboration of composite materials. This review aims at providing a guide to CNF chemical pretreatment possibilities, optimize its production, and exhaustively report the available CNF and BC chemical modification techniques capable of producing high value-added materials.
Keywords: CELLULOSE PRETREATMENT; NANOFIBRILLATED CELLULOSE (CNF); BACTERIAL CELLULOSE; CHEMICAL MODIFICATION; ADSORPTION; GRAFTING